Open High School Program during Pandemic an Assessment: Basis for Program Enhancement - Timula, Janette M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Education plays a significant part in moulding the future of our young generation of learners and leaders, and recognized as a basic human right. It is an essential requirement for a person’s well-being. Education is an absolute right of every individual which will enable him/her to become a productive citizen, globally competitive and can make the difference to every individual’s quality of life. Schools faced unprecedented challenges to ensuring sustainable education during the novel coronavirus COVID-19 pandemic. As school closures due to COVID-19 separate students from structured routines and educational supports, the number of disengaged students may continue to grow. Accordingly, this quantitative study reported that the Rizal High School in Pasig City, Philippines continuously adopted Open High School Program to meet with the disengaged students in the new normal. The subjects of the study were the twenty randomly selected teachers of Rizal High School during the School Year 2020-2021. It was found out that summary of the assessment on the open high school program based on goals and objectives has a general weighted mean of 3.75 interpreted as strongly agree, implies that the goals and objectives of the Open High School Program were well planned, organized and clearly defined. Such that, the methods of teaching had a general weighted mean of 3.46 "Strongly Agree." Further, there was an issue in the open high school program learners that needs to be addressed.